SURFACE CHARACTERIZATION AND POINT OF ZERO CHARGE OF A CU²+ BASED COORDINATION COMPOUND AND ITS POTENTIAL FOR ADSORPTION OF POLLUTANTS - Sunday E., Elaigwu; Vincent O., Adimula; Olanrewaju A., Rasheed; Bisola R., Efunwole; Adedibu C., Tella (FUDMA Journal of Sciences, 2025)
Coordination polymers or compounds have been used as multifaceted materials for different application due to their porosity and high surface area, availability of multicomponent organic ligands and the possibility of using different inorganic metal atoms in their fabrication. Thus, in this study, a Cu²+ based coordination compound was synthesized from 1,2,4,5–benzenetetracarboxylic acid, 4–aminomethylbenzoic acid, NaOH and copper (II) acetate monohydrate by refluxing and characterized for its potential application in the removal of pollutants. Characterization techniques studied includes Fourier Transform Infrared (FTIR) spectroscopy, Transmission Electron Microscopy (TEM), Brunauer–Emmett–Teller (BET) surface area analysis, and X-ray Photoelectron Spectroscopy (XPS). FTIR confirmed successful metal–ligand coordination through O–H, C=O, and Cu–O vibrations, while TEM revealed a porous and heterogeneous morphology, the BET analysis gave a surface area of 72.20 m²g-¹. XPS spectra showed the coexistence of Cu²+ and Cu+ oxidation states. The point of zero charge (PZC) determined by the pH drift method was 5.7, suggesting selective adsorption of anionic pollutants below this pH and cationic pollutants above it. These results demonstrate that the Cu2+ based coordination compound exhibits typical characteristics that favours adsorption of pollutants.